The response of sub‐Mediterranean grasslands to rainfall variation is influenced by early season precipitation. Issue 4 (10th August 2016) - Chelli, Stefano; Canullo, Roberto; Campetella, Giandiego; Schmitt, Armin Otto; Bartha, Sándor; Cervellini, Marco; Wellstein, Camilla
Abstract: Question: Climate change will likely modify patterns of precipitation, with an expected increase in intra‐annual variability and increased frequency and magnitude of extreme events. The Mediterranean area is expected to be very sensitive to such events because water availability is already limited. However, the effect of precipitation variability on ecosystem services, such as plant productivity, is little known. What is the short‐term effect of an experimental precipitation gradient on above‐ground net primary productivity (ANPP) of two contrasting sub‐Mediterranean grassland ecosystems? How does early season precipitation, i.e. dry or wet spring, influence ANPP? Do the functional groups of grasses and forbs differ in their response? Location: Torricchio Nature Reserve, Central Apennines, Italy. Methods: We selected two grasslands characterized by contrasting geophysical and soil chemical parameters (north‐ and south‐facing slopes). In both sites, during two climatically different years, mid‐season (summer) precipitation was manipulated in order to obtain a gradient of rainfall availability, comprising additional rainfall, ambient rainfall conditions and rainfall reduction. The above‐ground biomass, subdivided according to the functional groups of forbs and grasses, was collected at the end of each treatment period. Results: A significant increase in ANPP due to experimental increase in summer rainfall appeared in the year with the wet spring, but only in the mesic north‐facing slope. This response was driven by the increased productivity of perennial forbs, while grasses showed stable above‐ground production. In contrast, in the year with the dry spring, ANPP did not respond to the experimental rainfall gradient, meaning that a dry spring leads to lower ANPP even under increased summer rainfall. The variability of ANPP increased significantly in the xeric south‐facing slope in the year with the wet spring, most likely reflecting indirect effects of small‐scale heterogeneity such as variations in soil depth. Conclusions: Intra‐annual precipitation variation can have noticeable implications for sub‐Mediterranean montane grassland agriculture: to avoid degradation due to overgrazing, livestock pressure should be limited in years with a spring drought, regardless of summer precipitation, especially in mesic grasslands. Abstract : The present study highlights the importance of intra‐annual precipitation variation in conditioning ANPP of sub‐Mediterranean montane grassland. In case of wet spring, experimental summer water addition produced an increase of ANPP driven by perennial forbs, only under mesic conditions. On the contrary, in the year with the dry spring, ANPP did not respond to the experimental rainfall manipulation.